2022
DOI: 10.3390/jpm12091412
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Distress and Stress among Patients with Diabetes during COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: The prevalence of mental health disorders has increased during the COVID-19 pandemic. Patients with chronic diseases, such as diabetes, are a particularly vulnerable risk group. This study aims to assess the levels and prevalence of anxiety, distress, and stress in patients with diabetes during the COVID-19 pandemic. A systematic review was conducted in CINAHL, Cochrane, LILACS, Medline, SciELO, and Scopus in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 95 publications
2
9
1
Order By: Relevance
“…Furthermore, the COVID-19 pandemic may exacerbate the risk for depression among individuals with chronic illnesses ( Chen et al, 2020 ; Özdin and Bayrak Özdin, 2020 ; Luo Y. et al, 2020 ; Wang C. et al, 2020 ). According to a meta-analysis to assess the levels and prevalence of anxiety, distress, and stress in patients with diabetes during the COVID-19 pandemic, the prevalence of anxiety in type 2 diabetes patients was 20 and 36% in diabetes distress ( García-Lara et al, 2022 ), which were higher than those in the pre-pandemic period [18% ( Chaturvedi et al, 2019 ) and 29.4% ( Huynh et al, 2021 ), respectively]. Similarly, a study in China on 658 patients with breast cancer found that severe anxiety and depression during the COVID-19 pandemic were 8.9 and 9.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the COVID-19 pandemic may exacerbate the risk for depression among individuals with chronic illnesses ( Chen et al, 2020 ; Özdin and Bayrak Özdin, 2020 ; Luo Y. et al, 2020 ; Wang C. et al, 2020 ). According to a meta-analysis to assess the levels and prevalence of anxiety, distress, and stress in patients with diabetes during the COVID-19 pandemic, the prevalence of anxiety in type 2 diabetes patients was 20 and 36% in diabetes distress ( García-Lara et al, 2022 ), which were higher than those in the pre-pandemic period [18% ( Chaturvedi et al, 2019 ) and 29.4% ( Huynh et al, 2021 ), respectively]. Similarly, a study in China on 658 patients with breast cancer found that severe anxiety and depression during the COVID-19 pandemic were 8.9 and 9.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with previous research, indicating that as individuals age, distress related to diabetes intensifies. 11 , 26 , 27 The correlation highlights the challenges older clients encounter in harmonising diabetes management with family tasks, emphasizing the need for targeted healthcare strategies and support to address their unique concerns. Chima et al argues that healthcare delivery system in Malawi should encompass specialized counselling, targeted education, and community outreach to support older patients living with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disease increases the risk of the patient suffering an emotional and/or behavioral disorder, especially in times of social crisis such as that experienced with the COVID-19 pandemic [ 76 ]. This relationship has been demonstrated, with different levels of intensity and frequency, for the signs and symptoms of depression [ 77 ].…”
Section: Discussionmentioning
confidence: 99%